Copper-catalysed enantioselective Michael addition of malonic esters to β-trifluoromethyl-α, β-unsaturated imines. Issue 18 (13th April 2017) - Espinosa, Miguel; Herrera, Jorge; Blay, Gonzalo; Cardona, Luz; Muñoz, M. Carmen; Pedro, José R.
Abstract : A diastereo- and enantioselective Michael addition of methyl malonate to β-trifluoromethyl unsaturated imines is presented. Abstract : Copper triflate-BOX complexes catalyse the enantioselective conjugate addition of methyl malonate to β-trifluoromethyl-α, β-unsaturated imines to give the corresponding enamines bearing a trifluoromethylated stereogenic centre with good yields, and diastereo- and enantioselectivities. The usefulness of the method has been shown with the synthesis of optically active β-trifluoromethyl δ-amino esters and optically active trifluoromethyl piperidones.